MODERN METHODS OF PHLEGMONA TREATMENTWITH TYPE 2 DIABETES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
One of the most difficult and urgent problems of modern purulent surgery is the treatment of patients with phlegmons of the face and neck. This pathology is characterised by wide prevalence, difficulties in diagnostics at the early stage of the disease and severe course, often leading to lethal outcome. In patients diagnosed with phlegmons of the face or neck is often observed a decrease in immune status, which leads to a protracted course of the disease. In the presence of severe concomitant pathology, especially in the elderly and elderly, immunodeficiency leads to frequent complications.